The Influence of Career Choice Intentions on New Venture Creation in Algeria, Sierra Leone, and South Africa - Fragoso, Rui; Pereira, Renato (Senate Hall, 2022)
This paper analyses the influence that career choice intentions, including entrepreneurial intentions, have on new venture creation among African university students. In addition to that, we explore how social context may affect new venture creation, considering the inner circle of entrepreneurs, the organizational environment and the broader environment. To test our hypotheses, we used data from the 2018 Global University Entrepreneurial Spirit Students’ Survey (GUESSS), focusing on university students from Algeria, Sierra Leone and South Africa. Our findings provide evidence that, in these countries, career choice intentions to become an entrepreneur —either immediately after graduation or five years after graduation— are a good predictor of current new venture creation by university students. We also found an important role of the effectiveness of entrepreneurship education courses for determining new venture creation. Our investigation contributes to filling the gap in the link between career choice intentions and entrepreneurial behavior in Africa.
Keywords: career choice intentions|new business creation|university students|nascent entrepreneurs|entrepreneurial behavior|Africa